Jatropha curcas: A sustainable feedstock for biodiesel synthesis - Mohammed, Nurudeen Ishola; Kabbashi, Nassereldeen Ahmed (Nova Science Publishers, 2016)
The development of biodiesel as a renewable fuel is primarily dependent on two major implements encountered in the fossil fuel consumption. These constraints include dwindling oil reserves leading to probable dry-out of the resource in time and pollution related impact due to release of obnoxious gases when combusted. Oil seed price accounts for about 75% of the production cost on average , thereby, effort to abate this high cost adopts the use of low grade resources such as waste cooking oil (yellow grease) animals fats (tallow) and trap grease (brown grease). Nevertheless, uncertainty surrounding the availability of these materials calls for utilization of non-edible oil crop of which Jstropha stands prominent. Owing to the chemical composition of Jatropha, its properties and health related issues, a number of operations had been considered for a holistic biofuel development recording an unprecendted success relative to other non food materials. In this chapter, we presented the significance of Jatropha curcas oil and the dependence of the feed stock to production route selection. The use of various catalytic approaches was explored and the trends in the production capacities in different locations of the world. Findings revealed that, of more than 350 oil seed crops identified as potential feedstock for biodiesel development, the relevance of biodiesel Jartopha curcas stands out due to the advantage of its oil content, physical and chemical features, emission characteristics and it propensity to be used in all routes for biodiesel production. Jatropha biodiesel showed unrivalled conformity with standard specifications, hence it use in compression ignition engine pose no engine malfunction and undesirable byproducts as against other oil seed crop. Thus, it is a sustainable resource of immense benefit and relevance in biodiesel industry.